1995
DOI: 10.1007/3-540-58843-4_13
|View full text |Cite
|
Sign up to set email alerts
|

A formal scheme for avoiding undecidable problems. Applications to chaotic behavior characterization and parallel computation

Abstract: In this paper we intend to analyze a chaotic system from the standpoint of its computation capability. To pursue this aim, we refer to a complex chaotic dynamics that we characterize via its symbolic dynamics. We show that these dynamic systems are subjected to some typical undecidable and polinomially uneomputable problems. Our hypothesis is that these limitations depend essentially on the supposition of the existence of a fixed universal alphabet. The suggestion is thus of justifying a contextual redefinitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Two classes of logical symbols with their relations constituted via a common causal relation from the denoted object! It is evident that such a solution of the reference problem can be implemented only in a NC model where <v,w,z> can be interpreted as cognitive agents, particularly as (pseudo-)cycles of the same chaotic attractor, as we and others demonstrated elsewhere (See [30,18,31,32]; [33,34,35]). …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Two classes of logical symbols with their relations constituted via a common causal relation from the denoted object! It is evident that such a solution of the reference problem can be implemented only in a NC model where <v,w,z> can be interpreted as cognitive agents, particularly as (pseudo-)cycles of the same chaotic attractor, as we and others demonstrated elsewhere (See [30,18,31,32]; [33,34,35]). …”
Section: Discussionmentioning
confidence: 91%
“…a finitistic computational procedure always convergent in polynomial time, even in chaotic dynamics [30].…”
Section: Double Saturation S/p and Its Implementationmentioning
confidence: 99%
“…In the naturalistic approach the mathematical laws of physics and their evolution are based on the evolution of the universe, because there is mutual determination between the mathematical laws and the physical processes. The principle of this approach is named computational coarse graining (Perrone 1995;Basti & Perrone & et al 1995;1996). Secondly, the studies on entropy and on the inflation of the universe revealed that the gravitational force can be interpreted as the entropic force that generates information.…”
Section: Towards the Theory Of Informationmentioning
confidence: 99%
“…This complexity in-deed makes inapplicable to deterministic chaos classical statistical methods of signal analysis. In the last four years, however, one of us, developed a new effective technique of pseudo-cycle extraction of any length, with a computation time growing only linearly with the cycle length [42][43][44][45]. We have the definitive experimental evidence that this method, based on the new foundational ideas discussed in the next Section, can extract practically all the pseudo-cycles of a chaotic dynamics.…”
Section: 2 2 2 T H E O R E T I C a L L I M I T A T I O N S O F mentioning
confidence: 99%